NONPARAMETRIC METHOD FOR ESTIMATING THE SPOKEN LANGUAGE SOUND MULTIVARIATE PROBABILITY DENSITY FUNCTION - Sinitsyn, Rustem; Bokal, Zhanna; Zaets, Oleksandra; Kolchenko, Liliya; Tkachuk, Anton (Proceedings of National Aviation University (archive), 2006)
In the paper a new approach for estimating of the spoken language sound multivariate probability density is suggested. It is based on the use of a projection of a random process to the set of random variables, with the probability density defined as a product of two-dimensional densities. The estimates of two-dimensional probability densities are obtained with the help of filtering of the two-dimensional empirical characteristic function. Therefore, we are suggesting a nonparametric estimate of the characteristic function. On the basis of these estimates nonparametric algorithms of sound classification are constructed. Examples for the sound probability density function estimates are suggested.